Definition of left ventricular remodelling following ST-elevation myocardial infarction: a systematic review of cardiac magnetic resonance studies. (25th November 2020) - Legallois, D; Hodzic, A; Alexandre, J; Dolladille, C; Saloux, E; Manrique, A; Roule, V; Labombarda, F; Milliez, P; Beygui, F
Abstract: Background/Introduction: An increase in left ventricular volumes between baseline and follow-up imaging is the main criteria for the quantification of left ventricular remodeling after ST-elevation myocardial infarction, but without consensual definition. Purpose: We aimed to review the criterion used for the definition of left ventricular remodeling based on cardiac magnetic resonance imaging in studies including patients with ST-elevation myocardial infarction. Methods: A systematic literature search was conducted using MEDLINE and the Cochrane Library from January 2010 to August 2019. Thirty-seven studies involving a total of 4209 patients were included. Results: The median age of the patients was 59 years, 82% were male, and 93% underwent primary percutaneous coronary intervention. The median follow-up duration was 6 months (range, 3–12), and the second cardiac magnetic resonance session was performed at 6 months in 14 (38%) studies. Among these studies, 30 (81%) used a cut-off value for defining left ventricular remodeling, with a pooled left ventricular remodeling prevalence estimate of 22.8%, 95%-CI[19.4%-26.7%], and a major between-study heterogeneity (I 2 =82%). The seven remaining studies (19%) defined left ventricular remodeling as a continuous variable. A 20% increase in end-diastolic volumes or a 15% increase in end-systolic volumes between a baseline and a follow-up cardiac magnetic resonance imaging were the two most common criterion (13 [35%] and 9 [24%] studies, respectively). Seven studies used both end-diastolic and end-systolic vleft ventricular volumes. Conclusion(s): The definition of left ventricular remodeling using cardiac magnetic resonance following ST-elevation myocardial infarction is highly variable, among studies including highly selected patients. The most frequent left ventricular remodeling criterion were a 20% increase in end-diastolic volumes or a 15% increase in end-systolic volumes. A composite cut-off value of a 12% to 15% increase in end-systolic volume and a 12% to 20% increase in end-diastolic volume using a follow-up cardiac magnetic resonance imaging 1 to 3 months after myocardial infarction might be proposed as a consensual cut-off for defining adverse left ventricular remodeling for future large-sized, prospective studies with serial cardiac magnetic resonance imaging and long-term follow-up in unselected patients. Funding Acknowledgement: Type of funding source: None